(untitled) - Andrews, Ron L. (Melbourne, 1971)
This book introduce development of the modern economy. The physical framework and the water cycle. Landscapes and regions. The people population distribution and demography, urban settlement, roral settlement, argriculture...
Keywords: Nhật Bản,Japan; Điều kiện kinh tế,Economic conditions; 1945-1989,1945-1989